Implicit large eddy simulation of ship airwakes - Thornber, Ben; Starr, M.; Drikakis, Dimitris (Royal Aeronautical Society, 2010)
Implicit large eddy simulations (ILES) of two different Royal Navy ships have been conducted as part of the UK Ship/Air Interface Frame-work project using a recently developed very high order accuracy numerical method. Time-accurate CFD data for fourteen flow angles was produced to incorporate into flight simulators for definition of safe helicopter operating limits (SHOLs). This paper discusses the flow phenomenology for the different wind directions and where possible reports on the validation of the ILES results for mean and fluctuating velocity components and spectra against experimental data.
Keywords: high-resolution methods richtmyer-meshkov instability rayleigh-taylor instability reynolds-number flows numerical-simulation compressible flows wing flow turbulence database scheme